Approaches to metropolitan governance some policy considerations for reorganization in Metropolitan Manila - Oamar, Felipe V. (1977)
Western attempts at reforming urban systems along the metropolitan government concept have largely been failures, due to: (1) reformers' underestimation of the tough political obstacles facing their reorganizational proposals, and (2) widespread lack of effective governmental leadership to formulate comprehensive urban or metropolitan development policies. Three of these approaches are the: (a) federated approach, (b) urban county approach, and (c) interlocal cooperation. Attempts at reorganization of the Metropolitan Manila government (with its characteristic structural fragmentation, division of powers, and boundary inflexibilities) must account for the effects of changes within various levels of the system as well as the external sectors, e. g., the national government, the legislature, the private sector, the citizens of the community, and the trends and directions of change in the dynamics among these systems.
Keywords: Metro Manila -- Politics and government; Local government; Reorganization; Public administration